Perbedaan Edukasi Risiko Tinggi Kehamilan Audio Visual dan Buku KIA terhadap Pengetahuan dan Sikap Ibu Hamil - Royani Chairiyah (Jurnal Skala Kesehatan, 2026)
Efforts to promote health through appropriate educational media, such as audio-visual media, are expected to improve the knowledge and attitudes of pregnant women towards these risks. The objective of this research is to analyze the difference in effectiveness of education through audio-visual media compared to the KIA Book on the knowledge and attitudes of pregnant women regarding high-risk pregnancies. Method: This study uses a quasi-experimental design with a pretest-posttest control group design. A sample of 40 pregnant women using total sampling technique, data were analyzed using T-test, Wilcoxon, Mann-Whitney, and Chi-square tests. Results: showed a significant difference in knowledge between the intervention and control groups (p < 0.001), with 70% of respondents in the intervention group having good knowledge compared to 33.3% in the control group. The Relative Risk (RR) value of 9.000 indicates that pregnant women who received education through video had a 9 times greater likelihood of having good knowledge. Additionally, there was a significant difference in attitudes (p < 0.001), where 85% of respondents in the intervention group showed a positive attitude compared to 43.3% in the control group, with an RR = 0.588, which means that the intervention group had a 41.2% protection against negative attitudes. Conclusion: Education using audio-visual media is more effective in increasing knowledge and shaping positive attitudes among pregnant women regarding high-risk pregnancies compared to the use of KIA Books. It is recommended for healthcare workers to use audio-visual media as an innovative health promotion medium in efforts to prevent pregnancy complications